Sport hunting and tourism in the twenty-second century: humans as the ultimate trophy. Issue 3 (30th May 2019) - Wright, Daniel William Mackenzie
Abstract : Purpose: This paper aims to address the potential of hunting humans as sport tourism activity in the twenty-second century. The paper explores past and current trends related to sport hunting, animal extinction, human violence and the normalisation of violence via fictional media. This paper paints a provocative picture of society with the aim of encouraging dialogue across the wider community regarding the challenges facing society in relation to practices related to sport hunting and tourism. Design/methodology/approach: This paper takes a scenario narrative approach in presenting potential discussion on the future of sport hunting as a tourism activity. The importance of narrative writing as a method to research is its ability in telling a story to the reader. By embracing diverse philosophical methods, this research draws on past and current trends via secondary data sources to justify the future scenario narrative. Findings: This paper presents interesting insights into the future of sport hunting and its potential relationship to tourism. However, considering the following quote, "Yet another uncertainty is that predictions themselves can alter the future – which, of course, is part of the motivation behind futurism" (Larson, 2002, p. 5), this paper concludes with a sobering message, if previous research as well as the ideas presented here are to become a future reality, one where humans hunt each other for sport, are we content to allow this to happen? Or do we want to encourage debate to ensure we create better futures? Originality/value: This paper offers original and novel research within the sport-tourism literature by taking a futures perspective and applying a scenario narrative approach. The paper offers original insight into attitudes towards sport hunting and its future potential, moving away from its traditions of hunting animals to hunting humans. This paper encourages debate around a taboo-subject, by drawing on a popular past-time, sport. Death is also universal, and by aligning the topic with sport and as a hunting activity, this paper is offering original approaches to addressing difficult questions that need to be asked.